2022
DOI: 10.4314/njp.v49i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of COVID-19 infection in children in Southern Nigeria

Abstract: Background: Corona virus disease 2019 (COVID-19) is a global pandemic that affects all age groups. Infected asymptomatic children can transmit the disease to vulnerable adults with co-morbidities resulting in severe disease in the latter. There are few reports of COVID-19 in children in Sub-Saharan Africa in general and in Nigeria in particular.Aim: To determine the prevalence, symptoms and risk factors for COVID-19 in Southern Nigerian children.Methods: This was a one-year retrospective cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Non COVID-19: 70%), and breathing difficulties occurring only in COVID-19-positive patients. Fever as a symptom of SARS-CoV-2 infection was reported with varying frequency in pediatric patients, ranging from 43.5% to 90.9% [7,14,[28][29][30][31][32][33][34]. The results obtained are similar to those reported by Alpcan et al [14], who identified fever as the most frequent symptom (61.3%) in patients infected with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 87%
“…Non COVID-19: 70%), and breathing difficulties occurring only in COVID-19-positive patients. Fever as a symptom of SARS-CoV-2 infection was reported with varying frequency in pediatric patients, ranging from 43.5% to 90.9% [7,14,[28][29][30][31][32][33][34]. The results obtained are similar to those reported by Alpcan et al [14], who identified fever as the most frequent symptom (61.3%) in patients infected with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 87%